Establishing research priorities for malaria elimination in the context of the emergency response to artemisinin resistance framework-the Cambodian approach. (December 2016) - Canavati, Sara; Lawford, Harriet; Fatunmbi, Bayo; Lek, Dysoley; Top-Samphor, Narann; Leang, Rithea; Dondorp, Arjen; Huy, Rekol; Kazadi, Walter
Abstract Background Countries of the greater Mekong subregion have made a transition from malaria control to an aim for falciparum and vivax malaria elimination. The elimination of falciparum malaria will have to be achieved against a background of increasing artemisinin and multi-drug resistance. This ambitious goal requires an operational research (OR) agenda that addresses the dynamic challenges encountered on the path to elimination, which will need to be flexible and developed in close relation with the cambodian national programme for parasitology, entomology and malaria control (CNM). In Cambodia, a number of meetings with stakeholders were convened by the CNM and emergency response to artemisinin resistance (ERAR) hub, producing an initial list of priority OR topics. The process and outcome of these meetings are described, which could serve as a template for other countries in the region. Methods A landscaping exercise was conducted to gather all past, on-going and planned malaria focussed OR activities conducted by the cambodian research consortium in Cambodia and categorized according to research theme. The six themes included (1) malaria epidemiology, surveillance and response, (2) malaria case management, (3) malaria vector control, (4) malaria behavioural issues, (5) malaria clinical studies, and (6) other vector-borne diseases (dengue, neglected tropical diseases, soil-transmitted helminths). The different themes were discussed in small focus groups, which made an initial prioritization list which was then presented to a plenary group for further discussion. This produced a list of research questions ranked according to priority. Results OR priorities produced by the thematic groups were discussed in the plenary meeting and given a priority score by group voting. A list of 17 OR questions were developed, finalized and listed, which included questions on surveillance, active case detection and treatment efficacy. Conclusion This paper describes ERAR's work on supporting Cambodia's transition to malaria elimination by identifying national operational research priorities. ERAR has initiated and currently plays a critical role in the development of country specific research agendas for malaria elimination. The first example of this has been the described exercise in Cambodia, which could serve a template for setting OR priorities in the wider region.